Development of the Explosion and Fire Safety System of Oil Extraction Production - Viktorovich, Shevko Vladimir (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses ways to improve the fire and explosion safety system of oil extraction plants within the framework of the requirements of regulatory and technical documents.